Structure of russian students by the enrollment status - V. F. Pugach (Высшее образование в России)
The article dwells upon the dynamics of the number of students, students’ admission andproduction of specialists by the mode of study, peculiarities of state and non-state higher education establishments through dynamics of students’ groups of different modes of study. The paper reveals greater number of extramural students rooted in the overall trend for extramural study mode coupled with rising number of students of nonFstate educational establishments with the extramural mode being introduced still more intensively.